Revision of Cystomastacoides van Achterberg (Hymenoptera: Braconidae) with the description of two new species from south India - Ranjith, A.p.; Priyadharsanan, Dharma Rajan; Nasser, M (Zootaxa, 2018)
The rare rogadine genus Cystomastacoides van Achterberg is known from four species distributed in the Australian and Oriental regions. The genus is recorded for the first time from the Indian subcontinent with the descriptions of two new species, C. sachini Ranjith sp. nov. and C. yuvraji sp. nov. from south India. A key to the extant species is provided.